The Impact of the Covid – 19 Pandemic on Runway Service Life : (Case Study: Soekarno Hatta International Airport) - Garin Yacub; Ary Setyawan; Dewi Handayani; Jhon Hardy Purba (International Journal of Engineering Continuity, 2024)
Government policies that carry out large-scale social restrictions during the Covid-19 period have had an impact on reducing air traffic both for landings and takeoffs, which will have an impact on the life of runway services. Service life is the strength of road pavement in standing the repetition of permit loads before experiencing failure, by knowing that the service life can be directly used to determine the right time for runway maintenance. The purpose of this research is to determine the impact of the Covid-19 pandemic on the life of runway services. The method used in this research is the FAA method with the help of FAARFIELD software, this software calculates the service life based on the CDF value of each aircraft. The data used is secondary data in the form of aircraft type data, CBR ground, and existing pavement data. From the results of the research, it is known that the COVID-19 pandemic has a positive impact on the life of runway service by increasing the life of runway service by 4 years, where in the condition of covid-19 conditions it has a CDF value of 0.20 with a service life of 19 years and in normal conditions the CDF value is 0.22 with a service life of 15 years. The results of this research contribute to decision-making in carrying out maintenance and repairs on the runway of Soekarno Hatta International Airport so that the runway can operate sustainably in accordance with performance requirements throughout the life of the plan, to maintain flight safety and comfort.